1986
DOI: 10.1254/jjp.41.393
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Studies on the TXA2 Synthetase Inhibitor (E)-3-[p(1H-lmidazol-1-Ylmethyl)Phenyl]-2-Propenoic Acid (OKY-046)

Abstract: Abstract-The effects of (E)-3-[p-(1H-imidazol-1-ylmethyl)phenyl]-2-propenoic acid (OKY-046) on thromboxane A2 (TXA2) synthetase in vitro and on experimental animal models of sudden death and cerebral infarction were studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
1
2

Year Published

1990
1990
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(17 citation statements)
references
References 17 publications
1
13
1
2
Order By: Relevance
“…22) The COX inhibitors aspirin and indomethacin, TXA 2 synthesis inhibitor ozagrel, and TXA 2 receptor antagonist seratrodast have been used for the treatment of these diseases. 13,14,23) In the present study, we showed for the first time that the extract from Piper longum L. had an inhibitory effect on platelet aggregation as a TXA 2 receptor antagonist. These…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…22) The COX inhibitors aspirin and indomethacin, TXA 2 synthesis inhibitor ozagrel, and TXA 2 receptor antagonist seratrodast have been used for the treatment of these diseases. 13,14,23) In the present study, we showed for the first time that the extract from Piper longum L. had an inhibitory effect on platelet aggregation as a TXA 2 receptor antagonist. These…”
Section: Discussionsupporting
confidence: 53%
“…10) TXA 2 -induced platelet aggregation is important for thrombus formation in vascular beds, and because of this nonsteroidal anti-inflammatory drugs (NSAIDs) and TXA 2 synthase inhibitor such as aspirin, indomethacin, and ozagrel are clinically used for reducing TXA 2 -mediated platelet aggregation by decreasing TXA 2 synthesis in platelets. 13,14) Piper longum L., which has been used as a spice, contains various constituents such as piperine, piperlongumine, and b-(3,4,5-trimethoxyphenyl)propionic acid (TMPPA). Piper longum L. has also been used as a crude drug to improve intestinal disorder, asthma, and poor peripheral blood circulation in Asia.…”
mentioning
confidence: 99%
“…There have been several reports indicating that antiplatelet agents exert beneficial effects in this model (10,11,21). The interesting finding of the pres ent study is that the Ca-antagonist benidipine, which did not show any antithrombotic effects, exhibited be neficial effects of AA-induced cerebral infarction.…”
Section: Discussionmentioning
confidence: 64%
“…Ozagrel is an inhibitor of thromboxane A 2 synthetase and has already been launched on the market as an antithrombic and antiasthmatic drug. [7][8][9] The stereoselective outcome with excellent Z-selectivity in the Sn(OSO 2 CF 3 ) 2 -mediated HWE reactions can be rationalized in terms of a six-membered transition state proposed by us.…”
mentioning
confidence: 78%